Effect of Ti ion doping on electrochemical performance of Ni-rich LiNi0.8Co0.1Mn0.1O2 cathode material. (20th December 2019) - Zhang, Dengke; Liu, Yan; Wu, Lei; Feng, Liwei; Jin, Shuangling; Zhang, Rui; Jin, Minglin
Abstract: The effects of various Ti concentrations doping on the electrochemical properties of LiNi0.8 Co0.1 Mn0.1 O2 (NCM 811) sample were systematically studied. The XRD, EDS and XPS analyses indicated that the Ti-ion was substituted the occupied sites of Li and transition metal on the crystal structure. It also led to the increase of lithium interlayer spacing and the decrease of transition metal interlayer slab. The secondary particle size distribution of the 0.005 mol Ti-doped in LiNi0.8 Co0.1 Mn0.1 O2 approximated to normal distribution. It showed multi-layer performance with high capacity (214.9 mAh g −1 at 0.1C), good rate performance (165.02 mAh g −1 at 1 C, 136.9 mAh g −1 at 5 C) and more excellent cyclic stability (77.01% after 150 t h at 1 C and 86.54% after 50 t h at 5 C). TEM studies revealed that the structural degradation on NCM 811 primary nano-particle could be effectively suppressed by the effect of Ti ions doped. The results demonstrated that doping of Ti content had superior advantages for LiNi0.8 Co0.1 Mn0.1 O2 cathodes. Highlights: The synergistic effect of the proper Ti-doped and pressing treatment reduced the cation mixing effect of the material. The secondary particle size distribution of NCMT 0.005 material approximated to normal distribution. 0.005 moles Ti-doped of LiNi0.8 Co0.1 Mn0.1 O2  cathode material delivered greater rate performance. 00.005 moles Ti-doped of LiNi0.8 Co0.1 Mn0.1 O2  cathode material showed excellent cycle stability.